123k views
2 votes
Subtract 9t*3-3t+8 and t*2-8t+4 from the sum of 12t+8 and t*2 - 10t +3.



User Mazhar MIK
by
5.2k points

1 Answer

3 votes

⇒Find the sum of 12t+8 and
t^(2) -10t+3

⇒For sum we add:


=(12t+8)+(t^(2) -10t+3)\\=12t-10t+8+3+t^(2) \\=2t+11+t^(2)

⇒The next step is to subtract
9t^(3) -3t+8 and
t^(2) -8t+4 from the answer we got above.


=(2t+11+t^(2) )-(9t^(3) -3t+8)-(t^(2) -8t+4)\\=2t+11+t^(2) -9t^(3) +3t-8-t^(2) +8t-4\\=2t+3t+8t+11-8-4+t^(2) -t^(2) -9t^(3) \\=13t-1-9t^(3) \\

⇒The answer is shown above.

User Sdfsdf
by
5.5k points